The effect of honey cocktail supplement on macular thickness, retinal nerve fiber layes thickness and optic berve head parameters in post-menopausal women - Sivagurunathan, Premala Devi (2016)
Introduction Menopause is an integral part of a woman’s life. The clinical changes that occur during this period of life not only involve vasomotor, genitourinary, sleep disturbances and mood changes but also involve ocular structures such as tear film, lens, intraocular pressure, ocular blood flow and the retina. Apart from hormone replacement therapy (HRT), many other alternative therapies including honey showed promising effect in relieving menopausal symptoms, treating ocular diseases and maintain ocular functions. Objective To compare mean macular thickness, retinal nerve fiber layer (RNFL) thickness and optic nerve head (ONH) parameters with and without honey cocktail supplement in post-menopausal women. Methods This is a prospective randomized controlled trial conducted in Hospital Universiti Sains Malaysia between March 2014 and July 2015. A total of 60 post-menopausal women who fulfilled the selection criterias were selected and randomized into 2 groups using randomized opaque envelope technique “HONEY COCKTAIL” and “NO HONEY”. Baseline macular thickness, RNFL thickness and ONH parameters were taken using Cirrus HD-OCT machine for both groups by blinded trained personnel. Participants in the “HONEY COCKTAIL” group were instructed to take honey cocktail from the honey cocktail sachets provided for a total of 3 months duration. The dosing was 1 sachet containing 20 grams per day consumed straight from the sachet without dilution. Participant in the “NO HONEY” group were not given any placebo. After 3 months, the macular thickness, RNFL thickness and ONH parameters were repeated using the same machine, same technique and by the same blinded medical personnel. Statistical analysis was performed using SPSS version 22.0. Results A total of 60 participants were recruited (30 participants in each honey cocktail and no honey group). The mean global macular thickness was significantly thicker in post-menopausal women with honey supplement 3 months post supplement therapy (p = 0.002). There was also a significant difference in the mean change of global macular thickness at 3 months post supplement therapy between the 2 groups (p < 0.001). The mean global RNFL thickness was significantly higher in post-menopausal women with honey supplement 3 months post intervention (p = 0.033). There was also a significant difference in the mean change of global RNFL thickness at 3 months post supplement therapy between the 2 groups (p < 0.001). There were no significant difference in the ONH parameters in post-menopausal women with and without honey cocktail supplement 3 months post supplement therapy. There was significant difference in the mean change of rim area (p = 0.003), cup area (p = 0.001) and cup-disc-ratio (p <0.001) at 3 months post supplement therapy between the 2 groups. Conclusion Honey cocktail was shown to be beneficial and protective in improving macular thickness, RNFL thickness and ONH parameters in post-menopausal women.